THE INHIBITING FACTORS ON STUDENTS’ SPEAKING SKILL - Zuhra, Zuhra; Ega Revita; Nurul Fajri (LPPM - Universitas Serambi Mekkah, 2024)
This research intended to figure out the main cause of inhibiting factors in Speaking, the causes of that factor, and how to overcome the problem. Qualitative approach used to conduct the research. The subjects were students of VIII-4 graders at MTs.S Babun Najah Banda Aceh. Some instruments were questionnaire and semi-structured interview guide. The data were analysed qualitative descriptively. The results of questionnaire and interview revealed that three inhibiting factors in speaking English were articulation, lack of motivation, and pronunciation. The most inhibiting factor reached the highest percentage was pronunciation and it was a part of linguistic factors. This factor could be occurred because the students did not recognize the symbols of words. The students faced difficulty when they wanted to pronounce the words correctly, and when it happened the students commonly lost or became a trigger when they expressed their ideas English words are different from how they were written and pronounced. Hence, the students need to learn how to recognize the words’ symbols of English to ease them to make sounds (pronounce) the words consistently. To overcome the problems, this research suggested to the Englis teacher to use Audio-Lingual Method to improve students' pronunciation.